(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
The current work presents an experimental demonstration of the impact of two-phase flow mixture (water and air) temperature on the pressure across the bend’s upstream and downstream sides as well as the bend itself, as it is crucial for understanding and optimizing industrial processes. The test section in this study comprises a horizontal section, a vertical section, and a bend section, all made of PVC-U material with an inner diameter of 68 mm. The bend section has a curvature radius to diameter ratio (R/D) of 8. Pressure was monitored using six sensors over the test length for a range of water flow rates 18 to 42 and air flow rates 4 to 18 at various mixture temperatures. The obtained experimental pressure drop results were also compared to already previously published models to evaluate their performance in predicting pressure drop in conditions with heat transfer but no boiling. Based on the experimental result, the pressure across the test section increases with increasing temperature in a situation in which mixture viscosity is not dominated by liquid viscosity due to its high volume flow rate. Also, the pressure drop across the bend is higher at a lower air flow rate compared to a higher air flow rate at the same water flow rate and mixture temperature at room temperature, but as the mixture temperature increases, the pressure drop at a high air flow rate will be higher compared to a low air flow rate.